Role of Vacuum Therapy in Treatment of Infected Pseudoaneurysmectomy Wounds: A Clinical Approach - Elgazzar , Mohammed Hashem; Elhaig , Omar Mokhtar Ibrahim; Al-Fattah , Mohammed Abd (Research Highlights in Disease and Health Research Vol. 1, 2023)
Infected pseudoaneurysmectomy wounds pose a significant challenge to any vascular surgeon. Delayed wound healing is a major concern in such complicated and chronic wounds with co morbidities. It causes pain, morbidity, prolonged treatment, and necessitates major reconstructive surgery, which imposes a significant social and financial burden. This chapter aims to evaluate the results & benefits brought by the topical application of VAC in patients with infected pseudoaneurysmectomy wounds. This study was conducted on 15 patients of various ages and both genders at Al-Azhar University Hospitals and Matariya Teaching Hospital. The findings showed that In correlation of duration of VAC with other fields of assessment there was statistical significance for duration with sex (P value; 0.043), HCV infection (P value; 0.032), IV drug abuse (P value; 0.003), ESRD (P value; 0.003), region of pseudoaneurysm (P value; 0.003), size of wound at start (P value; 0) & number of dressings (P value; 0). There was statistical significance for complications incidence with the presence of HCV infection (P value; 0.029) & wound size (P value; 0.029) in the correlation of complications incidence with the disciplines of assessment. The study concluded thatVAC is useful in the treatment of infected pseudoaneurysmectomy wounds. It stabilises the wound, reduces edoema, reduces bacterial load, improves tissue perfusion, and stimulates granulation tissue proliferation. It is simple and effective in terms of reducing wound size, treatment duration, and complication incidence.